2015
DOI: 10.1371/journal.pone.0135428
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution and Evolution of Gray Matter Damage in Different Populations of Multiple Sclerosis Patients

Abstract: BackgroundBoth gray-matter (GM) atrophy and lesions occur from the earliest stages of Multiple Sclerosis (MS) and are one of the major determinants of long-term clinical outcomes. Nevertheless, the relationship between focal and diffuse GM damage has not been clarified yet. Here we investigate the regional distribution and temporal evolution of cortical thinning and how it is influenced by the local appearance of new GM lesions at different stages of the disease in different populations of MS patients.MethodsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 44 publications
8
45
0
Order By: Relevance
“…While MS is generally thought to be a demyelinating disease, it is now known that gray matter is also significantly affected 21 . Differential patterns in gray matter damage may contribute to the differences in the BOLD responses between voiders and dysfunctional voiders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While MS is generally thought to be a demyelinating disease, it is now known that gray matter is also significantly affected 21 . Differential patterns in gray matter damage may contribute to the differences in the BOLD responses between voiders and dysfunctional voiders.…”
Section: Discussionmentioning
confidence: 99%
“…While MS is generally thought to be a demyelinating disease, it is now known that gray matter is also significantly affected. 21 Differential patterns in gray matter damage may contribute to the differences in the BOLD responses between voiders and dysfunctional voiders. Our group has previously found that MS patients with VD had significantly less similar functional connectivity patterns compared to patients with MS who were able to void suggesting a possible failure in the cortical compensation mechanism for voiding.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the development of CLs has been reported more frequently in the temporal and frontal lobes, while the occipital lobe is less affected (Calabrese, Favaretto, Martini, & Gallo, ). With regard to CLs distribution in different disease subtypes, one recent study reported that in CIS and early RRMS patients, the most affected areas were the fronto‐temporal regions, while CLs were more widespread in late RRMS and SPMS (Calabrese et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a three-dimensional version (3D-DIR) allows for a shorter acquisition time and a reduction in artefacts (Roosendaal et al, 2009). With the application of these techniques, several studies have demonstrated that CLs are a typical finding in all phenotypes and stages of MS, including clinically isolated syndrome (CIS) (Calabrese et al, 2007(Calabrese et al, , 2008Geurts et al, 2005) and radiologically isolated syndrome (Calabrese & Gallo, 2009;Giorgio et al, 2011), although they are more represented in the progressive forms and with longer disease duration (Calabrese et al, 2015;Kutzelnigg et al, 2005;Mike et al, 2011;Roosendaal et al, 2009).…”
mentioning
confidence: 99%
“…For instance, the consensus is that MS lesions disrupt the corresponding white matter pathways, leading to dysfunction. However, recent research has suggested that physical and cognitive disabilities seem to correlate better with damage to grey matter than with the lesion load of white matter in MS patients [42]. Future research is needed to elucidate the association between structural damage (grey matter and white matter) and causal changes involving cortical and subcortical RSNs in MS. Second, it should be noted that the observed correlation in the acute phase was relatively weak, and no correlations were observed in the remitting phase of RRMS.…”
Section: Limitationsmentioning
confidence: 99%